Preparation and Energy Release Properties of nB@F2603@CL-20 Microspheres by Electrospray - Jie Yao; Yanjie Huang; Kanghua Chang; Jianxin Nie; Xueyong Guo; Chen Shen; Shi Yan (Metals, 2022)
Nano-boron, as a potential high-energy additive due to its high calorific value, is widely studied in propellants, explosives, and thermites. However, the unexpected agglomeration of surface oxidation hinders its further application, especially in the casting of energetic materials. The fluorine-modified nano-boron nB@F2603 and nB@F2603@CL-20 preagglomerated microspheres were prepared by electrospray to improve the ignition and combustion reactions and the rheological properties of boron-containing casting systems. Sphericity microspheres could be obtained by controlling the voltage and propulsion rate. The morphology and elemental distribution of the microspheres were characterized by the scanning electron microscope (SEM), energy-dispersive X-ray spectroscopy (EDS), and X-ray diffractometer (XRD). Results showed that the particle size of the microspheres ranged from 4 to 14 µm. Boron, fluorine and nitrogen were uniformly distributed on the surface of the microspheres. XRD results showed that CL-20 in nB@F2603@CL-20 microspheres was β-crystal. The thermal reaction properties were studied by differential scanning calorimetry, thermogravimetry and mass spectrometry (TG-DSC-MS), oxygen bomb calorimeter, laser ignition, and volume combustion cell test. Results showed that F2603 could significantly promote the ignition and combustion of nano-boron, causing higher energy release and pressurization rates, and lower ignition temperature. Adding CL-20 to the microspheres could also greatly promote the reaction rates and energy release. The hydrophobicity and corrosion resistance of the structures were also studied, and results showed that the preagglomerated microspheres had good stabilities. Therefore, fluorine-containing nB@F2603 and nB@F2603@CL-20 microspheres might be used in composite energetic materials, replacing nano-boron.